Development of grass jelly processing using modified starches and higher efficient extraction method - Leelawat, B.; Permpoonchokkana, P.; Jirapornsirikun, T. (International Journal of Agricultural Technology, 2020)
The grass jelly stalks was extracted using pressure cooker at 117oC for 30 minutes and followed by boiling under atmospheric pressure for 60 minutes to get the total solid content (%) in grass jelly solution resulted non-significantly different from the traditional boiling for 3 hours. The pea starch and 3 types of modified starches (KSA1502, ET50, and ESH15) at 5 % by solution weight were improved the grass jelly texture. The grass jelly from KSA1502 had hardness, springiness and gumminess that did not significantly different from the control (tapioca starch). Finally, the grass jelly solution was extracted by reducing grass jelly stalks for 30% from the control formula, and using 2% KSA1502 with gelatin 2.5 % together with varying tapioca starch to 4 levels as 0, 1, 2 and 3% by solution weight. It was found that the formula using 2% KSA1502 along with 1% tapioca starch and 2.5% gelatin by weight to receive the best texture properties and sensory scores in all attributes.